The Notion of Text and the Notion of Document - what Difference does it make? - Skare, Roswitha (Nordlit, 2009)
The origins of the notion of both text and document can be traced back to antiquity. Over the course of their respective histories – which I will not go into at this juncture – the meanings of both terms have evolved. Beyond the commonly used meanings, there are numerous other usages in various fields of specialization.